(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Starting from the traumatic experience of the Covid-19 pandemic, this article reflects on the theatrical performance A Sociedade dos Anticorpos (The Society of Antibodies), staged in 2023, by the collective Poéticas do ENTRE, particularly the scene Sintoma Luto (Mourning Symptom), which seeks to rewrite the history of the pandemic by evoking the absences and erasures resulting from power struggles over the right to memory. The article also contextualizes the Brazilian pandemic period and the necropolitics, a concept by Achille Mbembe, which, together with the ideas of Ileana Dieguez, Amílcar Borges de Barros, Michael Pollak, Leda Maria Martins, and Emerson Pereti, informs the reflection.